2014
DOI: 10.1038/cddis.2013.508
|View full text |Cite
|
Sign up to set email alerts
|

HER2/ErbB2 activates HSF1 and thereby controls HSP90 clients including MIF in HER2-overexpressing breast cancer

Abstract: Overexpression of the human epidermal growth factor receptor-2 (HER2) in breast cancer strongly correlates with aggressive tumors and poor prognosis. Recently, a positive correlation between HER2 and MIF (macrophage migration inhibitory factor, a tumor-promoting protein and heat-shock protein 90 (HSP90) client) protein levels was shown in cancer cells. However, the underlying mechanistic link remained unknown. Here we show that overexpressed HER2 constitutively activates heat-shock factor 1 (HSF1), the master … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 59 publications
6
74
0
4
Order By: Relevance
“…Hsf1 þ/À Neu þ mice also showed reduced association of the Hsp90 client protein c-RAF with HSP90 and reduced levels of AKT-ERK1/2 signaling (16). Similar findings with respect to stabilization of Hsp90 client proteins by Her2/HSF1 axis came from a study where inhibition of Her2 signaling resulted in the inhibition of HSF1 activity (phosphorylation) and the destabilization of HSP90 clients including MIF (macrophage migration inhibitory factor) and AKT (17). Recent studies have demonstrated that overexpression of mutant p53 also activates EGFR/Her2, leading to enhanced PI3K and MAPK signaling, which results in the phosphorylation and activation of HSF1 (32).…”
Section: Ras-mapk and Mutant P53 Signaling In Tumorssupporting
confidence: 65%
See 1 more Smart Citation
“…Hsf1 þ/À Neu þ mice also showed reduced association of the Hsp90 client protein c-RAF with HSP90 and reduced levels of AKT-ERK1/2 signaling (16). Similar findings with respect to stabilization of Hsp90 client proteins by Her2/HSF1 axis came from a study where inhibition of Her2 signaling resulted in the inhibition of HSF1 activity (phosphorylation) and the destabilization of HSP90 clients including MIF (macrophage migration inhibitory factor) and AKT (17). Recent studies have demonstrated that overexpression of mutant p53 also activates EGFR/Her2, leading to enhanced PI3K and MAPK signaling, which results in the phosphorylation and activation of HSF1 (32).…”
Section: Ras-mapk and Mutant P53 Signaling In Tumorssupporting
confidence: 65%
“…Experimental evidence suggests that loss of HSF1 results in the decreased stability of HSP90 client proteins (mostly kinases) and inhibits their downstream signaling (described in the more detail in the following sections; refs. 16,17).…”
Section: Hsf1 and Protein Homeostasismentioning
confidence: 99%
“…Downstream signaling pathways are activated upon ErbB2 receptor activation through either heterodimerization with ligand bound EGFR, ErbB3, or ErbB4 family receptors, or in presence of overexpression of ErbB2 due to gene ampliication, by ligand independent homodimerization [12]. The homo/heterodimerization promotes the receptor activation that in turn leads to tyrosine phosphorylation of the C-terminal residues.…”
Section: Molecular Mechanisms Of Erbb2 Activationmentioning
confidence: 99%
“…Moreover, it was recently demonstrated in HER2-overexpressing breast cancer cells that HSF1 is constitutively phosphorylated and activated by the HER2-PI3K-AKT-mTOR signaling pathway and controls Hsp90 client proteins, including MIF (macrophage migration inhibitory factor, a tumor promoting protein) [25].…”
Section: Hsf1 Regulates Ldha Transcription and Stimulates Glycolysis mentioning
confidence: 99%